Discovery of Levetiracetam (Keppra(R)): The first SV2A ligand for the treatment of epilepsy - Klitgaard, Henrik (Henry Stewart Talks, 2013)
Levetiracetam, Antiepileptic Drug Discovery, Levetiracetam in electroshock and PTZ seizures, Protection against seizures in rat model, Levetiracetam activity in GAERS model, Impact on cognitive function, Hyper-synchronization / excitability inhibition in vitro, Effect on development of amygdala kindling, Effect on seizures in genetic models of epilepsy, Inactivation of sodium channels, Reduction of current through T-type Ca channels, Levetiracetam mechanism of action, SV2 proteins: candidates for the LEV binding site, SV2A cloning and binding studies, Levetiracetam studies in SV2A (+/-) mice, Profile of new class of antiepileptic drugs